If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-30-5x=5(-3x+6)
We move all terms to the left:
-30-5x-(5(-3x+6))=0
We calculate terms in parentheses: -(5(-3x+6)), so:We get rid of parentheses
5(-3x+6)
We multiply parentheses
-15x+30
Back to the equation:
-(-15x+30)
-5x+15x-30-30=0
We add all the numbers together, and all the variables
10x-60=0
We move all terms containing x to the left, all other terms to the right
10x=60
x=60/10
x=6
| 3|x+6|-2=9 | | 1+5b+3b=9 | | 2x-12=-(-3+3x) | | 3a÷5=4 | | 5=n/3+10 | | 4x+7=5-3x | | 8(y=4)-2(y-1)=70-3y | | 5^x-2=4^2x-4 | | -6a+3=6a-3 | | 16-x-x=18 | | 2x+3=3(x-4) | | 0.4x+(0.6*12x)=27 | | 7x+10=68 | | 2-16t=6(-3t+2 | | 1+x/10=0 | | 0.4x+(x(0.6*12))=27 | | 11=y+8 | | 8x+17 = 121 | | 3(m-8)=-38+5m | | 14x-7=49 | | 3^2x+6=2^x+3 | | 2a+2a=-8 | | 5(h-3)=6 | | 2n-3n=6 | | 12(x+56)=32 | | 4y+3y=56 | | -2x+5x=x | | 10x+5=-30 | | 5(h−3)=6 | | -3x+9x=-24 | | -8/3+4=b | | -8y-y=-54 |